2019
DOI: 10.1111/ger.12444
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different irrigation protocols on microhardness and flexural strength values of young and aged crown dentin

Abstract: Objective To investigate the effect of different irrigation protocols on microhardness (MH) and flexural strength (FS) values of young and aged crown dentin. Background In addition to ageing, root canal irrigation might also affect the mechanical properties of coronal dentin walls. Materials and Methods One hundred and twenty dentin bars (2 mm × 2 mm × 8 mm) were obtained from the crowns of extracted, non‐caries, human molars of young and older patients (n = 60 bars; average patient ages: 16.7 and 65.4, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 36 publications
0
27
0
1
Order By: Relevance
“…Oldaged dentine was reported to have greater hardness and elastic modulus, and mineral content compared with young dentine (Xu et al 2014). A previous study, however, reported similar changes in the root canal dentine after EDTA irrigation in both young and old age groups (Pedersen et al 2020).…”
Section: Discussionmentioning
confidence: 88%
“…Oldaged dentine was reported to have greater hardness and elastic modulus, and mineral content compared with young dentine (Xu et al 2014). A previous study, however, reported similar changes in the root canal dentine after EDTA irrigation in both young and old age groups (Pedersen et al 2020).…”
Section: Discussionmentioning
confidence: 88%
“… The study by Pedersen et al 30 includes additional SEM analysis for smear layer removal efficacy's evaluation. …”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed to the physiochemical changes related to the aging process of dentin represented by increase in inorganic part of mineral content and decrease in organic part of collagen. Deposition of peritubular dentin increases leading to the narrowing of the dentinal tubules and complete obliteration of others which has a direct effect on the efficacy of the irrigating solutions (1) . Laser irradiation can cause morphological and chemical alterations in dentin represented by the evaporation of the dentin organic matrix leaving pores and spaces (29) .…”
Section: Discussionmentioning
confidence: 99%
“…These modifications take place until the majority of tubule lumens have calcified and the sclerotic tissue is apparent. Changes in mechanical parameters like fracture resistance, flexure strength, and microhardness are also recorded, in addition to microstructural changes (1) .…”
Section: Introductionmentioning
confidence: 99%